Non-traditional security in East Asia a regime approach - Pacheco Pardo, Ramon; Reeves, Jeffrey (Imperial College Press, 2016)
In a changing security environment shaken by the United States' pivot to Asia, China's rise, growing economic interdependence, new institutional frameworks, and long-standing tensions, regional security dynamics within East Asia have changed profoundly.